Analysis of the teacher perspective about the Implementation of a Colour-Adaptive Lighting System in Smart Classrooms - Quiles-Rodríguez, José; Palau, Ramon (Journal of Ecohumanism, 2025)
This study explores primary school teachers’ perspectives on the implementation of a colour-adaptive lighting system in smart classrooms. While previous research has primarily focused on the effects of correlated colour temperature (CCT) on learning and cognition, studies on coloured lighting remain limited. To address this gap, a focus group discussion was conducted with seven primary school teachers in Andalusia, Spain, each with varying levels of experience and exposure to colour lighting in classrooms. The discussion examined general environmental factors, emotional responses, the perceived benefits and challenges of colour lighting, and potential solutions for its integration into smart classrooms. A thematic analysis, supported by AI-assisted coding, identified key themes such as the role of environmental factors in learning, the influence of coloured lighting on student engagement, and the practical barriers to its implementation. Findings highlight teachers’ recognition of environmental conditions as influential in the learning process, concerns regarding classroom adaptability, and the need for flexible, research-informed lighting solutions. The study contributes to the ongoing discourse on smart classroom design by integrating qualitative insights from educators, emphasizing the necessity of a user-centered approach to educational technology.